An effective growth method to improve the homogeneity of relaxor ferroelectric single crystal Pb(In1/2Nb1/2)O3‐ Pb(Mg1/3Nb2/3)O3‐PbTiO3. Issue 2 (13th January 2014) - Wang, Xian; Zhang, Haiwu; Lin, Di; Wang, Sheng; Zhao, Xiangyong; Chen, Jianwei; Deng, Hao; Li, Xiaobing; Xu, Haiqing; Luo, Haosu
<x xml:space="preserve">Abstract</x> An effective method to improve the segregation is characteristics of multi‐round growths and gradient composition raw materials in vertical Bridgman technique. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>